Data analytics : 31st British International Conference on Databases, BICOD 2017, London, UK, July 10-12, 2017, Proceedings /: 31st British International Conference on Databases, BICOD 2017, London, UK, July 10-12, 2017, Proceedings. (2017) - Unknown
No abstract available